The Solonian Council of 400 and the Anarchies in Post-Solonian Athens - Valdés Guía, Miriam (Pnyx: Journal of Classical Studies, 2025)
This paper analyses the composition of Solon’s Council of 400, its relationship with the four tribes, its role in the election of the archons and the periodicity of this body in relation above all to the periodic crises (anarchies) that occurred after the Solonian legislation until Damasias (594–582 BCE). Just as these anarchies took place “every four” years, so too did the penteteric or megala Panathenaia begin to be held “every four years” a little later (566 BCE). I suggest that this periodicity may have been related, in some way, to the quadrennial election of the Solonian Council in the month of Hekatombaion.